Alcohol dehydrogenase and cytochrome P450 2E1 can be induced by long-term exposure to ethanol in cultured liver HEP-G2 cells - Balusikova, Kamila; Kovar, Jan (In vitro cellular & developmental biology. Animal, 2013)
It has been shown in previous studies that liver HEP-G2 cells (human hepatocellular carcinoma) lose their ability to express active alcohol dehydrogenase (ADH) and cytochrome P450 2E1 (CYP2E1). Although both are ethanol-inducible enzymes, short-term exposure to ethanol does not cause any changes in expression or activity in cultured HEP-G2 cells. Therefore, we tested the effect of long-term exposure to ethanol on the expression and activity of both ADH and CYP2E1 in these cells. The expression of ADH and CYP2E1 was assessed at the mRNA and/or protein level using real-time PCR and Western blot analysis. Specific colorimetric assays were used for the measurement of ADH and CYP2E1 enzymatic activities. Caco-2 cells (active CYP2E1 and inactive ADH) were used as control cells. Significantly increased protein expression of ADH (about 2.5-fold) as well as CYP2E1 (about 1.6-fold) was found in HEP-G2 cells after long-term (12 mo) exposure to ethanol. The activity of ADH and CYP2E1 was also significantly increased from 12 ± 3 and 6 ± 1 nmol/h/mg of total protein to 191 ± 9 and 57 ± 9 nmol/h/mg of total protein, respectively. We suggest that the loss of activity of ethanol-metabolizing enzymes in cultured HEP-G2 cells is reversible and can be induced by prolonged exposure to ethanol. We are therefore able to reactivate HEP-G2 cells metabolic functions concerning ethanol oxidation just by modification of in vitro culture conditions without necessity of transfection with its side effect - enzyme overexpression.
Keywords: Gene Expression Regulation, Neoplastic; cytochrom P-450 CYP2E1; buňky Hep G2; regulace genové exprese u nádorů; Carcinoma, Hepatocellular; oxidace-redukce; Alcohol Dehydrogenase; Animals; lidé; játra; enzymová indukce; Humans; zvířata; ethanol; Ethanol; Cytochrome P-450 CYP2E1; Hep G2 Cells; hepatocelulární karcinom; alkoholdehydrogenasa; apoptóza; Enzyme Induction; Liver; Liver Neoplasms; Oxidation-Reduction; nádory jater; Apoptosis